Addition of Lemna (Lemna minor) in Goat Rations: Effect on Milk Composition and Fermentation Product Characteristics - Hartati, Hartati; Prayitno, Caribu Hadi; Sumarmono, Juni (Jurnal Agripet, 2025)
This study evaluated the effect of Lemna minor supplementation in dairy goat feed on milk fat and fatty acid composition. The results showed that the addition of L. minor significantly altered the milk fat profile, which may influence the quality of fermented dairy products. Fresh goat milk and milk from goats fed with L. minor were used as the primary raw materials for producing fermented products such as yogurt and kefir. The objectives of the study were: (1) to compare the composition of fresh milk produced by goats fed a basal diet and those fed a diet supplemented with L. minor, and (2) to compare the characteristics and composition of fermented milk products, namely yogurt and kefir, made from both types of goat milk. The research was conducted as a laboratory experiment. The observed variables included fresh milk composition, viscosity, color profile of fermented milk, and fatty acid composition of the fermented products. The results indicated that both fresh goat milk and Lemna-supplemented goat milk met the Indonesian National Standard (SNI) for milk quality, with no significant differences between them. Viscosity differed between yogurt and kefir products, whereas the color profile was not influenced by the type of milk used. The saturated chain fatty acid (SCFA) content in Lemna goat milk was 8.91%, while in the fermented products it was 0.99% and 1.17%, respectively. The polyunsaturated fatty acid (PUFA) content in Lemna goat milk was 17.48%, decreasing to 15.20% in the fermented products.